The Effects of Source Cues and Issue Frames During COVID-19. Issue 3 (29th January 2022) - Case, Chandler; Eddy, Christopher; Hemrajani, Rahul; Howell, Christopher; Lyons, Daniel; Sung, Yu-Hsien; Connors, Elizabeth C.
Abstract: The health and economic outcomes of the COVID-19 pandemic will in part be determined by how effectively experts can communicate information to the public and the degree to which people follow expert recommendation. Using a survey experiment conducted in May 2020 with almost 5, 000 respondents, this paper examines the effect of source cues and message frames on perceptions of information credibility in the context of COVID-19. Each health recommendation was framed by expert or nonexpert sources, was fact- or experience-based, and suggested potential gain or loss to test if either the source cue or framing of issues affected responses to the pandemic. We find no evidence that either source cue or message framing influence people's responses – instead, respondents' ideological predispositions, media consumption, and age explain much of the variation in survey responses, suggesting that public health messaging may face challenges from growing ideological cleavages in American politics.